Experimental Thrombosis on a Collagen Coated Arterioarterial Shunt in Rats: A Pharmacological Model to Study Antithrombotic Agents inhibiting Thrombin Formation and Platelet Deposition - Freund, Monique; Mantz, Françoise; Nicolini, Philippe; Gachet, Christian; Mulvihill, Juliette; Meyer, Laurent; Beretz, Alain; Cazenave, Jean-Pierre (Thrombosis and Haemostasis, 1993)
A rat thrombosis model was developed to assess the efficacity of antithrombotic drugs. It had the following characteristics: controlled hemodynamic and rheological conditions corresponding to arterial flow, a collagen coated surface as a relevant thrombogenic stimulus, a method of measurement allowing dynamic monitoring of thrombus formation and the possibility to assess the thrombus structure. A shunt composed of polyethylene and silicone catheters, including in the middle of the shunt a collagen coated glass capillary, was inserted between the two primitive carotids of the rat. The duration of patency of the shunt was recorded using a thermic probe fixed on its central part. In this model, the patency of the shunt was 539 ± 55 s. Platelet and fibrinogen-fibrin accumulation in successive one centimeter segments along the shunt were measured using 111In labeled platelets and 125I labeled fibrinogen. Platelet accumulation occurred on the collagen coated surface and at the junctions between the different components of the shunt, where flow was disturbed. The effects of four antithrombotic agents were measured: aspirin, clopidogrel, heparin and r-hirudin. Clopidogrel, heparin and hirudin significantly prolonged patency duration of the shunt, whereas aspirin was inactive. Aspirin did not reduce platelet or fibrinogen-fibrin accumulation on the collagen coated surface. Platelet accumulation on the collagen surface was significantly lower in the clopidogrel group (50 mg/kg) than in the group treated with heparin (500 U/kg), demonstrating the direct antiplatelet effect of clopidogrel. Hirudin at doses giving similar values of APTT as heparin (500 U/kg) prolonged the occlusion time to over 2 h while the heparin occlusion time was only 20 min. We conclude that this experimental arterioarterial thrombosis model is sensitive to both antiplatelet and anticoagulant agents, allowing discrimination between antiplatelet and anticoagulant mechanisms of thrombosis prevention. The technique is easily performed in a small animal, fast and reproducible, and thus comparable to primate models for use in the screening of new antithrombotic drugs.